The Selection and Appointment Process of Village Officials: North Lampung as a Case Study - Musholeh, Tol'ah; Dinata, Muhammad; Haryadi, Selamet (LifeSciFi, 2023)
The process of appointing village officials is strictly regulated by Law No. 6 of 2014. Village officials are designated by the village head following consultation with the subdistrict head, who acts on behalf of the regent or mayor. This research delves into the appointment and dismissal processes of village officials within the context of Sidodadi Village, North Lampung, Indonesia. It underscores deviations from prescribed regulations, notably the absence of a formal selection team and the prevalence of character-based assessments. Community perceptions raise concerns about age limits and perceived direct appointments, which may hinder effective governance. To address these issues, the study recommends incorporating integrity requirements for village head candidates and enhancing socialization efforts to align with existing regulations, ultimately aiming to improve village governance practices. The findings shed light on the challenges and opportunities in optimizing local administration and service delivery.